Batch growth kinetic studies for elimination of phenol and cyanide using mixed microbial culture. (June 2016) - Singh, Neetu; Balomajumder, Chandrajit
Abstract: The efficiency of a mixed microbial culture to eliminate phenol and cyanide from aqueous solution was estimated in a batch process. The influence of initial concentration of phenol and cyanide on the microbial growth was calculated for the range of initial concentration between 50 and 1500 mg/L of phenol and 5–150 mg/L of cyanide. A maximum specific growth rate of 0.0663 h −1 was observed at 250 mg/L of phenol and 0.143 h −1 at 25 mg/L of cyanide concentration in the growth medium. The specific growth rate of the culture followed substrate inhibition kinetics. Monod, Haldane, Edward, Yano and Koga, Luong, Han-Levenspiel, and Powell growth kinetic models were used to determine the growth kinetics of mixed culture. Edward, Luong and Han and Levenspiel models were established as best fit to the specific growth rate data for phenol. However, for cyanide Haldane and Edward models were found to be best with lowest Marquardt's percent standard deviation (MPSD) values. The degradation kinetics of phenol and cyanide was found to follow a three-half order model at all initial concentrations with lowest MPSD value.